International Corporations as Actors in Global Governance Evidence from 92 Top-Managers in Germany and France - Baer, Maxim; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2013)
Global Governance describes on a normative level how companies can be responsible and sustainable actors in the international sphere. In times of globalization, failing financial systems and gridlocked political structures, these concepts gain critical importance. Maxim Baer revisits the discussion, leaves the traditional (3z(Binternational relations(3y (Bperspective behind and examines leadership strategies of top-executives in large companies that enable firms to be part of Global Governance structures. A second focus lies on a possible impact of national culture on business leaders and their respective attitude towards elements of Global Governance. A German-French comparison has been conducted.s
Global Governance -- Leadership -- Institutional Logic -- Neo-Institutional Theory -- Germany / France. National Culture.
Keywords: Social sciences; Social Sciences; Social Sciences, general